A Case of Prenatal Diagnosis of Trisomy 18 with Ultrasound - Yusrawati, Yusrawati; Kartika, Yudha M (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To report a case of trisomy 18 diagnosed in prenatal care. Methods: Case report. Case: A 24 years old primigravida woman was diagnosed with term pregnancy (37-38 weeks) with an intrauterine singleton live fetus with Edwards syndrome. In 15-16 weeks of pregnancy the omphalocele was discovered using ultrasound. Subsequently, amniocentesis was performed and the chromosome analysis result showed Edwards syndrome (47, XX +18). The patient chose to continue the pregnancy until term. In this patient, elective CS was performed at term pregnancy, involving teamwork between obstetrics and perinatology. A female baby was born weighing 1720 grams, 40 cm body length, and APGAR score of 5/7. The congenital anomalies discovered include umbilical hernia, rocker bottom feet, clenched hands, low set malformed ears, and a single umbilical artery. The baby was born with asphyxia, improved after resuscitation, and required treatment in the NICU. Pediatric surgeons planned umbilical hernia repair. Furthermore, because of the presence of suspected esophageal atresia, the baby was planned for gastrotomy, which was delayed because the baby was experiencing desaturation. Because of the unstable condition of the baby, echocardiography and gastrotomy were not done until the 18th day of treatment. At the 18th day, the baby’s condition deteriorated and the baby died with metabolic acidosis. Conclusion: Edwards syndrome can be diagnosed in the prenatal period by risk factors consideration, maternal serum markers, and ultrasonographic identification of organ abnormalities. [Indones J Obstet Gynecol 2015; 3-4: 234-238] Keywords: Edwards syndrome, prenatal diagnosis, trisomy 18, ultrasound